2022
DOI: 10.1101/2022.11.04.515189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Faecal microbiota transplantation from Alzheimer’s participants induces impairments in neurogenesis and cognitive behaviours in rats

Abstract: The gut microbiome is emerging as an important susceptibility factor in Alzheimers disease (AD) possibly due to the increased prevalence of pro-inflammatory genera in gut microbiota of AD participants. Microbiota-mediated changes in cognition and adult hippocampal neurogenesis (AHN), an important process for memory which is altered in AD, position the microbiota-gut-brain axis as a key regulator of AD. However, it is unknown whether gut microbiota alterations are the cause or consequence of AD symptoms. We tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 169 publications
0
2
0
Order By: Relevance
“…While a causal link between dysbiosis and disease is difficult to demonstrate in humans, dysbiosis is often suspected to have a role in the initiation, manifestation, and progression of disease. In animal models, however, the use of germ-free mice and the manipulation of the microbiome with populations of bacteria or faeces from patients with neurodegenerative diseases have provided evidence of causation [32,211,212].…”
Section: The Gut-brain Axis and Neurodegenerative Diseasesmentioning
confidence: 99%
“…While a causal link between dysbiosis and disease is difficult to demonstrate in humans, dysbiosis is often suspected to have a role in the initiation, manifestation, and progression of disease. In animal models, however, the use of germ-free mice and the manipulation of the microbiome with populations of bacteria or faeces from patients with neurodegenerative diseases have provided evidence of causation [32,211,212].…”
Section: The Gut-brain Axis and Neurodegenerative Diseasesmentioning
confidence: 99%
“…This coincided with alterations in microbial metabolites such as short-chain fatty acids (SCFAs; D’Amato et al, 2020 ) which have previously been shown to regulate host microglial maturation and function ( Erny et al, 2021 ). Moreover, using humanised models by transplanting FMT from older subjects with Alzheimer’s disease into microbiota-depleted naïve adult rats showed impairment in hippocampal neurogenesis accompanied with memory deficits, which correlated with clinical cognitive scores ( Grabrucker et al, 2022 ). Furthermore, young mice who received gut microbiota from aged donors suffered increased rates of mortality following ischemic stroke, along with increased levels of pro-inflammatory plasma cytokines and impaired motor strength ( Spychala et al, 2018 ).…”
Section: The Gut Microbiota Actively Contributes To Brain Health Duri...mentioning
confidence: 99%